Chapter Il metodo comparativo nello studio dei rapporti tra il Domostroj e i suoi equivalenti europei - Priadko, Eugène (Biblioteca di Studi Slavistici, 2017)
The article adresses the well-known question about the eventual links between the Old Russian Domostroi and the European domestic handbooks and focuses on the aporia to which lead all the previous comparative works. The methodological character of the impasse apears clearly when we analyze those works in the light of a clearly defined comparative method. As a result, the author suggests to address the relationships between the Domostroi and its European analogues no more from the traditional literary point of view but from a historical one.